2013
DOI: 10.1148/radiol.12112677
|View full text |Cite
|
Sign up to set email alerts
|

Hypovascular Nodules in Patients with Chronic Liver Disease: Risk Factors for Development of Hypervascular Hepatocellular Carcinoma

Abstract: Hyperintensity on T2-weighted images is an independent and strong risk factor at baseline for subsequent hypervascularization in hypovascular nodules in patients with chronic liver disease. Tumor volume doubling time of less than 542 days was associated with a high rate of subsequent hypervascularization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
117
3

Year Published

2013
2013
2018
2018

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 131 publications
(129 citation statements)
references
References 39 publications
9
117
3
Order By: Relevance
“…Well-differentiated HCCs tend to be slow growing, whereas moderately and poorly differentiated HCCs are fast growing, although there is overlap in the reported TVDTs of HCCs with varying degrees of differentiation (93,97,98). Imaging features associated with shorter TVDT include APHE (92,(99)(100)(101), presence of "washout" (100,102), T2 hyperintensity (99), and diameter less than 1 cm at baseline (94,103).…”
Section: Review: Li-rads Major Features For Hepatocellular Carcinoma mentioning
confidence: 99%
“…Well-differentiated HCCs tend to be slow growing, whereas moderately and poorly differentiated HCCs are fast growing, although there is overlap in the reported TVDTs of HCCs with varying degrees of differentiation (93,97,98). Imaging features associated with shorter TVDT include APHE (92,(99)(100)(101), presence of "washout" (100,102), T2 hyperintensity (99), and diameter less than 1 cm at baseline (94,103).…”
Section: Review: Li-rads Major Features For Hepatocellular Carcinoma mentioning
confidence: 99%
“…Hypointense lesions in the hepatobiliary phase of Gd-EOB-DTPA-enhanced MRI that show nonhypervascularity on dynamic imaging are commonly encountered, and it is recommended that these lesions be monitored closely due to their potential for malignancy and transitioning to HCC through a multistep progression of hepatocarcinogenesis [21,22,23]. Several studies have reported the outcome of patients with these hypointense lesions [22,23,24,25,26,27,28,29]; however, only a small number of such cases have been reported and all were from a single center. The present investigation was a longitudinal retrospective nationwide study that examined the natural outcome of nonhypervascular lesions in the hepatobiliary phase of Gd-EOB-DTPA-enhanced MRI.…”
Section: Introductionmentioning
confidence: 99%
“…In patients with chronic liver disease, hypovascular nodules detected on enhanced computed tomography or ethoxybenzyl diethylenetriamine magnetic resonance imaging, most of which are dysplastic nodules or early HCC, have the potential to progress to hypervascular HCC (19,20). Therefore, the American Association for the Study of Liver Disease Practice Guidelines recommends the early detection of HCC followed by appropriate treatment (21).…”
Section: Discussionmentioning
confidence: 99%